Schisandrin B Inhibits Cell Viability and Migration, and Induces Cell Apoptosis by circ_0009112/miR-708-5p Axis Through PI3K/AKT Pathway in Osteosarcoma - Wang, Bing; Wang, Xiaowei; Tong, Xing; Zhang, Yingang (Frontiers in Genetics, 2020)
Osteosarcoma is a primary tumor of bone and its incidence is increasing. Schisandrin B (Sch B), a generally used lignan in Chinese medicine, has been found to repress cancer progression. This study aims to reveal the effects and regulatory mechanism of Sch B in the viability, apoptosis and migration of osteosarcoma cells. In this study, we found circ_0009112 expression was higher and miR-708-5p expression was lower in SaOS2 and U2OS cells than in hFOB1.19 cells. Circ_0009112 expression was downregulated, but miR-708-5p was upregulated by Sch B treatment in a dose-dependent manner in SaOS2 and U2OS cells. Sch B exposure inhibited osteosarcoma development in vitro and in vivo; however, these effects were restored by circ_0009112. Furthermore, circ_0009112 acted as a sponge of miR-708-5p. Circ_0009112 regulated PI3K/AKT pathway after Sch B treatment by associating with miR-708-5p. Sch B exposure inhibited cell viability and migration, whereas promoted cell apoptosis by regulating circ_0009112/miR-708-5p axis through PI3K/AKT pathway in osteosarcoma cells. This study provided a theoretical basis for further studying osteosarcoma therapy with Sch B.